Investigating Speaking Difficulties of Senior High School Students: Linguistics and Psychological Problems - Wulandari, Nyimas Ayu; Amalia, Shynta; Ramdhani, Muhammad Iqbal (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The purpose of this study was to gain an understanding of the problems in communication experienced by senior high school students in Jambi City. Students in their final year of secondary education in Jambi City served as participants in this study. This study was carried out at SMAN 03, SMAN 08, and SMAN 11 Jambi City, all of which are recognized educational institutions. There were a total of 130 students in the tenth grade that took part in this research. The research was a quantitative study that was designed in the form of a survey. The questionnaire was the instrument that was employed for this study. There are a total of 25 questions on the questionnaire, all of which pertain to the difficulty that students have expressing themselves verbally regarding linguistics and psychological issues. The findings of this study also suggested that the students attending the three authorized institutions had the perception that psycholog